[Aerial looking west from the Poly P, 1968] - American Aerial Surveys, Inc.::::::::: (1969)
This aerial photograph captures eastern San Luis Obispo, Cal Poly including agricultural land, the Los Osos Valley, out to the coast. Morro Bay is visible in the distance, as is the Men's Colony and Camp San Luis. The date is based on similar aerial photographs in the archives that are dated January 18, 1968. The Yosemite residence halls are under construction, as is the pool. Visible is the aero hangar and runway. Image is stored in Flat File 93 in the archives.